Analysis of The Effect of Training Education (Diklat), Work Period and Career Development on Personnel Performance of The Medical aAnd Health Center of The Republic of Indonesia State Police - Deti Novalia; Zulkifli Rangkuti; Eddy Hermawan Hasudungan Panjaitan (Dinasti Publisher, 2026)
The purpose of this study is to describe and analyze the influence of education and training (diklat) on personnel performance, the influence of length of service on the performance of Pusdokkes Polri personnel, the influence of career development on personnel performance, and the influence of training, length of service, and career development simultaneously on the performance of Pusdokkes Polri personnel. There is an influence of training on work behavior , this can be seen from the calculated tvalue for Training (X1) of 4.804 while the ttable value for n = 115 is 1.981. So 4.804 > 1.981, then H0 is rejected and Ha is accepted. There is an influence of training on work behavior, this can be seen from tvalue for training (X2) is 8.434 while the ttable value for n = 115 is 1.981. So 8.434 > 1.981, then H0 is rejected and Ha is accepted. There is an influence of supervision on work behavior, this can be seen from The calculated tvalue for career development (X3) is 4.253 while the ttable value for n = 115 is 1.981. So 4.253 > 1.981, then H0 is rejected and Ha is accepted. There is an influence of training, length of service, and career development which jointly influence the performance of the personnel of the Indonesian National Police Health Center, this can be seen from the calculated Fvalue is 119.862 while the Ftable (a0.05) for n = 115 is 2.45. So the calculated F is > from the Ftable ( a0.05) or 119.862 > 2.45, with a significance level of 0.000 because 0.000 < 0.05